Impact of Practical Online Lessons on Chinese Medical Students’ Perception of Radiation Oncology - Ziye Zheng; Yuxuan Wang; Fuquan Zhang; Jiawei Zhu; Jing Shen; Qingyu Meng; Bei Wang; Bing Zhou; Wei Tian; Lihua Yu; Junfang Yan (Journal of Cancer Education, 2023)
Radiotherapy is an essential component of oncology treatment. It is imperative that clinicians and medical students have a fundamental understanding of radiotherapy. However, radiation oncology education is deficient worldwide. This study introduced an hour-long online Massive Open Online Course (MOOC) as a supplement to the basic curriculum for 8-year medical students at Peking Union Medical College and Tsinghua University in China. The students’ personal opinions and comprehension of radiation oncology therapy were assessed through pre- and post-test questionnaires before and after the MOOC study. The results indicated that the percentage of students interested in radiotherapy increased, and their knowledge of radiotherapy significantly improved after the online MOOC study, suggesting that short-term MOOC study may stimulate students’ interest in learning and improving their knowledge of radiation therapy. The study suggests that the combination of online and offline teaching may be a feasible way to develop radiation oncology education in the future.